Atypical Origin of Lateral Pectoral Nerve: A Case Report - Bidyarani Devi Loitongbam; Anjulata Rai; Jyoti Arora; Harshika Khatri (Journal of Clinical and Diagnostic Research)
In the present case, two Lateral Pectoral Nerves (LPN) were in the right axilla. The upper branch, superior LPN arose from the proximal part of the axilla deep to the clavicle from the anterior division of the upper trunk. This branch descends medially and enters the deep surface of the pectoralis major muscle. A larger LPN is seen originating from the distal part of the right lateral root of the median nerve at the lower part of the axilla, medial to the third part of the right axillary artery. This inferior LPN is 2 cm long, descends medially, and joins with the Medial Pectoral Nerve (MPN) forming ansa pectoralis. The branches from the ansa pierce the pectoralis minor muscle and enter the pectoralis major muscle. It supplies both the pectoral muscles. LPN fibers passing from the Lateral Cord (LC) through the lateral root of median have not been reported yet. The LPN is the main nerve of pectoralis major muscle. A thorough understanding of Pectoral Nerve (PN) anatomy is a must for surgeons practicing mastectomies, breast augmentation surgery, axillary dissection, harvesting pectoralis major muscle island flap, and dealing with trauma and fracture of the shoulder.